Powder Injection Molding an Alternative Method in the Manufacturing of Parts for Vehicles - Gonzalez-Gutierrez, Joamin; Emri, Igor (Anali PAZU, 2022)
Powder injection molding (PIM) is one of the most versatile methods for manufacturing small complex shaped components from metal, ceramic powders for the use in many applications. Interesting applications of PIM include the automotive and aerospace industries. PIM can be used to combine multiple parts into a single part with complex geometry, and parts are lighter since porosity remains in the final part while the fatigue resistance increases. Therefore, it can be said that PIM can help reduce the weight of moving vehicles, which is a major concern from the environmental and economic point of view. One of the main limitations of current PIM technology is the long debinding time, which is one of the steps within the process. This has been partially solved by introducing binder systems that undergo catalytic sublimation. However, current catalytic binders have the main problem of high viscosity. In this study, two ways to decrease the viscosity of PIM feedstock materials with polyoxymethylene were investigated. The first way was to reduce the average molecular weight of the binder and the second one to select a polydisperse particle size distribution with high maximum packing fraction.